1999
DOI: 10.1002/(sici)1097-0142(19991001)86:7<1263::aid-cncr23>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

P‐cadherin expression in breast carcinoma indicates poor survival

Abstract: Expression of P-cadherin in breast carcinoma is associated strongly with poor survival and constitutes an independent prognostic predictor. P-cadherin expression is a better indicator of clinical outcome than alterations in the expression of E-cadherin, N-cadherin, alpha-catenin, or beta-catenin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 0 publications
6
63
1
1
Order By: Relevance
“…The present study shows that P-cadherin expression is strongly associated with high histological grade of DCIS and with loss of ER, as already reported by two other studies in invasive ductal carcinoma [25,27]. Moreover, almost all P-cadherin-positive cases were also positive to c-erbB-2, and some have presented p53 immunoreactivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study shows that P-cadherin expression is strongly associated with high histological grade of DCIS and with loss of ER, as already reported by two other studies in invasive ductal carcinoma [25,27]. Moreover, almost all P-cadherin-positive cases were also positive to c-erbB-2, and some have presented p53 immunoreactivity.…”
Section: Discussionsupporting
confidence: 90%
“…P-cadherin, however, can be expressed in a subset of breast cancers [25,28]. Recently, Peralta Soler et al observed P-cadherin expression in invasive ductal carcinomas with higher histological grade and poor survival, suggesting that this protein could constitute a prognostic marker [27].…”
Section: Introductionmentioning
confidence: 99%
“…In this model, expression of P-cadherin is associated with poor survival and constitutes an independent prognostic indicator [34]; it is also associated with an infiltrative growth pattern [34]. This may argue in favour of a role for P-cadherin in the acquisition of more aggressive behaviour in breast tumours.…”
Section: Discussionmentioning
confidence: 89%
“…Recent publications on the expression of P-cadherin and breast cancer [25,34] showed an important role for this molecule in breast carcinogenesis. In this model, expression of P-cadherin is associated with poor survival and constitutes an independent prognostic indicator [34]; it is also associated with an infiltrative growth pattern [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, over expression of N-cadherin in E-cadherin-expressing breast cancer cells caused an increase in their invasive and metastatic potential [6], despite the vital role of E-cadherin in suppression of invasion and metastasis [2][3][4]9]. There is conflicting evidence regarding the role of P-cadherin in carcinogenesis with increased P-cadherin expression associated with poor survival in breast and ovarian cancer [10][11][12] or with better survival [13].…”
Section: Introductionmentioning
confidence: 99%